THE EFFECT OF VIDEO PUBLICATION ON PUBLIC INTEREST IN FOLLOWING SRIWIJAYA RANAU GRAN FONDO ACTIVITIES IN LAKE RANAU - Muhammad Ridho, Muhammad Ridho (CV. Cendikiawan Muda Sriwijaya, 2024)
The development of information technology is very rapid following the times where currently Digital Media is very important for disseminating information. The use of this fast-paced information technology is also used by Dinas Kebudayaan dan Pariwisata Provinsi Sumatera Selatan as an opportunity for a method of disseminating information in the form of activities carried out at Lake Ranau, so that researchers are interested in conducting research with the title